Pengaruh Kecerdasan Emosional, Motivasi Kerja Dan Sikap Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Padangsidimpuan - Aprina Yanti Rangkuti; Muhammad Hakim; Boga Pramukti; Yenny Yunita (Manajemen dan Bisnis, 2022)
Problem of this study is how influence of  emotional intellegence on employee’s performance. How influence of  job motivation on employee’s performance. How influence of  work attitude on employee’s performance. How influence of  emotional intellegence, job motivation and work attitude on employee’s performance. The purpose of this study to determine and analyze the effect of  emotional intellegence on employee’s performance. Determine and analyze the effect of job motivation on employee’s performance. Determine and analyze the effect of work attitude on employee’s performance. Determine and analyze the effect of emotional intellegence, job motivation and emotional intellegence on employee’s performance. Sample in the study is 34 employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate  emotional intellegence variable has a positive and no significant effect on employee’s performance.  Job motivation variable has a positive and significant effect on employee’s performance.  Work attitude variable has a positive and significant effect on employee’s performance.  Emotional intellegence, job motivation and work attitude variable’s has a positive and significant effect on employee’s performance.